Southerners Are Wiser Than Northerners Regarding Interpersonal Conflicts in China - Wei, Xin-Dong; Wang, Feng-Yan (Frontiers in Psychology, 2020)
Initial evidence suggests that cultural differences have consequences for wise reasoning (perspective taking, consideration of change and alternatives, intellectual humility, search for compromise, and adopting an outsider’s vantage point), with more reports of wise reasoning about interpersonal conflicts among Japanese (as compared to American) young and middle-aged adults. Similarly, we found that people from the rice-farming area of southern China also exhibited greater wise reasoning when they encountered conflicts with a friend or in the workplace than those from the wheat-farming area of northern China (N = 487, 25 provinces). The relationship between rice farming and wise reasoning was mediated by loyalty/nepotism. This research advances study of the relationship between wisdom and culture. It also provides evidence for the influence of social-ecological factors on wisdom and culture.